Evaluasi Pemanfataan Foto Udara untuk Perhitungan Volume StockROM 74 di PT Mitra Indah Lestasi - Audi Qhoryaty Salsabillah; Nia Kurniadin; Dwi Agung Pramono; Feri Fadlin (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2026)
Survey activities in the mining sector generally use terrestrial methods, total stations are one of the tools used. The use of total stations is considered inefficient because it requires many surveyors and takes a long time. Technological developments in the field of surveying allow the use of photogrammetry methods with drones/UAVs as tools for mapping in the mining sector, including in calculating the volume of stockROM (Run of Mine) using aerial photographs. The advantages of using this method include being able to cover a wider area in a relatively short time, surveyor efficiency, and more affordable costs. However, we still need to assess the quality and accuracy of stockROM volume calculations by comparing them to terrestrial topographic data. StockROM 74 PT Mitra Indah Lestari was taken as a sample in this study. Aerial photo data was processed using Agisoft Metashape to produce DEM data. The DEM was processed to produce contour data. On the other hand, this DEM was also processed to obtain point values using the extract value to point method using ArcGIS. Topographic data from measurements using a total station is used as a comparison. The three data sets—contour data, point data, and topography—were processed using a triangulation method using Minescape to generate StockROM volume values, which were then compared. The difference in volume between contour processing and topographic data is 6%, while between point processing and topographic data is 0.00197%.